Умова стійкості системи обслуговування GI/G/1 з T-поверненням заявок - Koba, E. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The author considers a GI/G/1 retrial queueing system in which delaed customers are directed to the "orbit" to be returned in a constant time T. Let a be the mean inter-arrival time, τ be the service time. Then, under the condition (T + τ) / a < 1 a steady-state regime of the system is proved to exist. It is shown that the stated condition cannot be essentially improved.